APLIKASI AGENS HAYATI Pseudomonas fluorescens P60 TERHADAP MUTU FISIOLOGIS BENIH DAN PERTUMBUHAN BIBIT PADI IR 64 - Navitasari, Lisa (Jurnal Agroteknos, 2013)
The  research  aims  to  study  (1)  testing  P.  flourescens  P60  for  physiological  seed quality, and (2) testing P. flourescens P60 on the growth of seedlings in the greenhouse. The results indicated presence of physiological quality of seeds, treatment of P. flourescens P60 had the same effect with the treatment benomil and distilled water with no significantly different results, as well as the treatment of P. flourescens P60 was able to maintain the quality of physiological germination rate above 80%. Results of application P. flourescens P60 on the growth of rice seedlings in the greenhouse, treatment of P. flourescens P60 with immersion time 15 minutes and 25 minutes, had the same effect with distilled water and benomil in seedling height, root length, and dry weight of seedling, but different in wet weight of seedling and root dry weight. Keywords : Pseudomonas flourescens P60, seed physiological quality, growth of seedlings.